Dissemination workshop report on livestock movement routes and resources maps in the southern Oromia and Somali regions, Ethiopia - Berhanu, Dagim (ILRI, 2024)
Livestock route and related resources mapping, understanding their status and better protection of the routes in the pastoral areas are the first steps towards developing the areas. With this regard, International Livestock Research Institute (ILRI), in collaboration with other partners, conducted participatory livestock routes and related resources mapping activities in selected pastoral woredas of the Oromia region and Somali region with European Union (EU) funded project, the so called Health of Ethiopian Animals for Rural Development (HEARD). Since December 2019, numerous activities have been conducted to map and validate the status of major routes through which livestock moves to markets, water points, health facilities and other related infrastructure in those regions. After completing the mapping and validation activities successfully, the dissemination workshop was organized by ILRI’s HEARD project on 23 October 2023, in Hawassa town. A total of 39 (38 male and 1 female) participants from ILRI, governmental offices at different levels, universities, research centres, pastoral community elders, development partners and professional associations attended the dissemination workshop. The workshop was organized in four sessions. In the first part of the workshop, the process and outputs of the mapping activity were communicated through a series of presentations. In the second session of the workshop, four separate breakout sessions were held and participants discussed and presented on the significance of the mapping activity and the role expected from each participant in using the mapping outputs for the pastoral community development agendas. In the third session, a question and answer session was held to clear up any misunderstanding about the mapping process and outputs and a panel discussion was held to discuss the way forward. Generally, the participants were very satisfied with the overall mapping process and outputs and vowed to own and follow future supporting, servicing and protection activities of the routes and resources mapped in the study areas. In the final session of the workshop, eight copies of a waterproof paper based map printed by the Ethiopian Mapping Authority (EMA) at a scale of 1:80 km were handed over to the Ministry of Agriculture and other stakeholders and the dissemination workshop was closed.